Neural substrates of figurative language during natural speech perception: an fMRI study - Nagels, Arne; Kauschke, Christina; Schrauf, Judith; Whitney, Carin; Straube, Benjamin; Kircher, TIlo (Frontiers in Behavioral Neuroscience, 2013)
Many figurative expressions are fully conventionalized in everyday speech. Regarding the neural basis of figurative language processing, research has predominantly focused on metaphoric expressions in minimal semantic context. It remains unclear in how far metaphoric expressions during continuous text comprehension activate similar neural networks as isolated metaphors. We therefore investigated the processing of similes (figurative language, e.g. “He smokes like a chimney!”) occurring in a short story. Sixteen healthy, male, native German speakers listened to similes that came about naturally in a short story, while blood-oxygenation-level-dependent (BOLD) responses were measured with functional magnetic resonance imaging (fMRI). For the event-related analysis, similes were contrasted with non-figurative control sentences. The stimuli differed with respect to figurativeness, while they were matched for frequency of words, number of syllables, plausibility and comprehensibility. Similes contrasted with control sentences resulted in enhanced BOLD responses in the left inferior (IFG) and adjacent middle frontal gyrus. Concrete control sentences as compared to similes activated the bilateral middle temporal gyri as well as the right precuneus and the left middle frontal gyrus. Activation of the left IFG for similes in a short story is consistent with results on single sentence metaphor processing. The findings strengthen the importance of the left inferior frontal region in the processing of abstract figurative speech during continuous, ecologically-valid speech comprehension; the processing of concrete semantic contents goes along with a down-regulation of bilateral temporal regions.